Group identity and discrimination in small markets: Asymmetry of in-group favors - Gerhard Riener; Alexander Schacht (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
We experimentally study the inuence of induced group identity on the determination of prices and beliefs in a small market game. We create group identity through a focal point coordination game. Subjects play a three-person bargaining game where one seller can sell an indivisible good to one of two competing buyers under four different treatments varying the buyer-seller constellation. We find evidence of in group favoritism on the buyer side. However we do not detect a lower ask prices for in-group sellers for in-group buyers, indicating that in-group favoritism is in favor of the more powerful market participan.
Keywords: C91; D45; L13; L14; 330; group identity; experiments; markets; bargaining; Verhandlungstheorie; Marktmechanismus; Test; Arbeitsgruppe; Soziale Rolle